Introduction of Special Issue “Religion and Refugee: Interdisciplinary Discussions on Transformative Human-Divine Interactions” - Horstmann, Alexander (Religions, 2021)
Mainstream works on refugees and religion have underlined the value that religion provides to émigrés [...]